Assessment of flexural strength of two self-curing acrylic resins containing pigment - Vicente Telles; Raphael M. F. Brito; Estela M. Jurach; Lincoln I. Nojima (Universidade Estadual de Campinas, 2015)
Aim: To assess the flexural strength of orthodontic acrylic resins from two different manufacturers (VIPI, OrtoCril versus Clássico, OrtoClas) by comparing pigmented resins to colorless ones. Methods: Resins of blue, yellow and green colors were studied. A total of 120 specimens were made and then divided into groups of 15 elements each, all having the same dimensions. Next, they were kept in aqueous medium until being subjected to mechanical testing. The flexural strength was tested in a universal test machine (EMIC DL 10000) in which the specimens were subjected to a gradual load until fracture occurred. Results: Pigmented resins had flexural strength values compatible with clinical use, being similar to those from colorless ones, except for OrtoClas green-colored and yellow-colored resins, which showed greater flexural strength. The OrtoClas green-colored resin was the most resistant to fracture (482.2 N), whereas the OrtoCril colorless resin was the least resistant (368.4 N). All OrtoClas resins showed higher strength values compared to OrtoCril resins of same color, except for the OrtoCril's blue-colored resin, which presented higher flexural strength than that of the other trademark. Conclusions: The use of pigments seems to have no effect on decreasing the flexural strength of self-curing acrylic resins. Therefore, pigmented resins are compatible with clinical use.